Impact of China’s Foreign Direct Investment (FDI) on EAC’s Economic Growth (2003-2022): An Econometric Analysis - Abadata, Clemence; Ze, Tian; Nyamekye, Abban; Amaniampong, Paulette (International Journal of Economics, 2025)
Purpose: This study examines the impact of China's Foreign Direct Investment (FDI) on economic growth within the East African Community (EAC) from 2003 to 2022. Methodology: Employing econometric techniques, including the Error Correction Model (ECM) and Ordinary Least Squares (OLS) regression, the research explores the dynamic relationships between Gross Domestic Product (GDP) and key determinants such as Gross Domestic Savings (GDS), Gross Capital Formation (GCF), Natural Resources (NR), and Trade Openness (TO). Findings: The results demonstrate that FDI, GDS, GCF, and TO significantly contribute to GDP growth, while NR exhibits a negative relationship with GDP. This negative effect may stem from the resource curse, where an overreliance on natural resources leads to economic volatility, weakens institutional frameworks, and diverts focus from other sectors. Additionally, fluctuations in global commodity prices can exacerbate economic instability. Unique Contribution to Theory, Practice and Policy: The study underscores the critical role of effective policy formulation and institutional capacity building to optimize the benefits of Chinese FDI, while addressing potential risks related to over-reliance and dependency.